2010
DOI: 10.1017/s0959270910000377
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year assessment of Asian Houbara Bustard populations: trends in Kazakhstan reveal important regional differences

Abstract: SummaryA sharp decline in the numbers of Asian Houbara Bustard Chlamydotis macqueenii towards the end of the 20 th century raised concerns about the conservation status of this species. Yet due to its large breeding range in the remote steppes and deserts of Central Asia and to its cryptic behaviour, it has been difficult to obtain enough comparable data to make reliable estimates of population trends. Here, we present the results of 10 years of extensive biannual surveys throughout southern Kazakhstan, consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…However, comparison with densities estimated for other Asian Houbara populations is problematic. Most recent studies used driven transects (Tourenq et al 2004(Tourenq et al , 2005Gubin 2008;Riou et al 2011) and each had methodological drawbacks. In Koshkin et al (2014) point counts were found to perform better than transects, at least in the conditions of the southern Kyzylkum.…”
Section: Houbara Population Estimatementioning
confidence: 99%
See 4 more Smart Citations
“…However, comparison with densities estimated for other Asian Houbara populations is problematic. Most recent studies used driven transects (Tourenq et al 2004(Tourenq et al , 2005Gubin 2008;Riou et al 2011) and each had methodological drawbacks. In Koshkin et al (2014) point counts were found to perform better than transects, at least in the conditions of the southern Kyzylkum.…”
Section: Houbara Population Estimatementioning
confidence: 99%
“…Gubin (2008) based multi-annual estimates for several areas in south-western Kazakhstan on numbers of individuals recorded along driven transects within a 200-m survey strip (range of 0.01-0.24 birds/ km 2 ); this may indicate relative abundance among areas, but as detectability was unknown it is not possible to account for undetected birds to estimate density. Although Riou et al (2011) and Tourenq et al (2004Tourenq et al ( , 2005 used distance analysis, distance measurements were not taken and the effective strip width (ESW) is not reported; also, analysis pooled across regions with differing relative abundance resulting in wide uncertainty, and timing and sex composition are not reported. Although more females are detected during driven transects (30 % of adult birds) than on point counts (7 %; Koshkin et al 2014), densities estimated by Riou et al (2011) and Tourenq et al (2004Tourenq et al ( , 2005 will have been underestimated to an unknown extent.…”
Section: Houbara Population Estimatementioning
confidence: 99%
See 3 more Smart Citations